KEWENANGAN PENUNTUT UMUM ANAK UNTUK MELAKUKAN PENUNTUTAN TERHADAP ANAK PELANGGAR HUKUM DALAM UPAYA DIVERSI YANG GAGAL (Studi kasus di Kejaksaan Negeri Kota Kediri) - Juliati, Atik; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2025)
The purpose of this study was to analyze the authority of the Child Public Prosecutor to prosecute children who break the law in a failed diversion attemp and to analyze the cause of the failure of the Child Prosecutor in seeking diversion for children as perpetrators of law violations.This study using empiris method with interviews and direct observation. Data collection techniques using primary data (structured interviews) and secondary data (observation and documentation). Sample collection techniques using purposive sampling method with 9 respondents are Child Public Prosecutor are 7 people and children who break the law are 2 people. The result of this study is The authority of the Child Public Prosecutor to prosecute children who break the law in failed diversion efforts is regulated in Law number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA), namely: The Child Public Prosecutor has the authority to prosecute; The Child Prosecutor has the authority to carry out the decisions of judges and court decisions that have permanent legal force; The Child Prosecutor has the authority to supervise the implementation of Conditional Criminal Decisions, Supervision Criminal Decisions and Conditional Release Decisions; The Child Prosecutor has the authority to complete certain case files and for this reason can carry out additional examinations before being transferred to the Court, which is coordinated with the Investigator. The cause of the failure of the Child Prosecutors in pursuing diversion for children as perpetrators of law violations is the public's lack of understanding about diversion and the purpose of carrying out diversion; The victim does not want to forgive the actions of the perpetrator's child; There is no agreement between the victim and the perpetrator's child regarding the nominal value of the amount of loss that must be returned; The perpetrator's child has been punished before (recidivist).